QUANTIFICATION OF CSF VELOCITY THROUGH THE NARROWEST POINT IN AQUEDUCT OF SYLVIA FOR NORMAL AND NORMAL PRESSURE HYDROCEPHALUS PATIENT BY CFD ANALYSIS - H, Thalakotunage A.; Sethaput, Thunyaseth (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
The aim of this comprehensive study is to quantify the velocity variation of cerebrospinal fluid (CSF) for narrowest point in aqueduct of Sylvia (AqSylv) of normal patients and normal pressure hydrocephalus (NPH) patient by corresponds to its concave shapes of anteriorly and inferiorly. T1-weighted 3-T magnetic resonance images (MRI) of the head in DICOM (Digital Imaging and Communications in Medicine) format were taken from three controlled patients whose were admitted to Thammasat Hospital, Thailand. Patients were 29 to 52 y of age with two normal patients and one (NPH) patient. DICOM files were three-dimensionally reconstructed by using 3D slicer software, and geometric information of an aqueduct for all three cases was noted. Solid models of the aqueduct for both normal patient and NPH condition were developed based on the geometric information. Computational fluid dynamics (CFD) were analyzed to quantify the CSF velocity variation throughout the narrowest point of the aqueduct for both cases, i.e. normal and NPH condition. Retrospective results of mathematical model for dynamics of CSF through the aqueduct of Sylvia based on an analogy of arterial dilation and contractionâ€ were used as initial data for ANSYS CFX analysis. The results showed the CSF flow through the aqueduct in a pulsatile pattern in both cases. At the narrowest point of the aqueduct, amplitude of peak CSF velocity for NPH patients was significantly higher than that of normal patient. CSF velocity variation throughout the aqueduct co-relates with the pressure gradient inside the aqueduct and increased in the third ventricle direction.